2021
DOI: 10.1088/1755-1315/709/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Maize Plant Due to Biochar Rice and Fertilizer of Soil in Kwala Bekala, North of Sumatera

Abstract: Inceptisol of Soil in Kwala Bekala Deli Serdang is the dominant agricultural land cultivated corn crop. However, the results obtained currently do not meet the desired target by farmers. A greenhouse study has been conducted to evaluate the response of corn plant growth through the application of rice husk biochar and manure on Ultisol of Soil in Kwala Bekala, Deli Serdang, North of Sumatera. This research was conducted using Randomized Block Design of Factor (RBDF) with 2 treatments. Treatment I used by bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Chekanaia et al (2018) showed that the appli cation of nitrogen (ammonium phosphate) and phos phorus (superphosphate) in beans doubled the dry weight and plant yield in both treatments compared to the control. Lubis et al (2021) stated that dry weight of rice and plant height that received ele ments increased under manure medium. Potassium reduces the negative effect of drought stress on leaf area index and plantʼs dry weight by increasing the ability of photosynthesis, the rate of CO 2 stabilizing with interference in osmosis, the activity of the enzyme Rubisco, and improving the synthesis and transport of dry matter (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Chekanaia et al (2018) showed that the appli cation of nitrogen (ammonium phosphate) and phos phorus (superphosphate) in beans doubled the dry weight and plant yield in both treatments compared to the control. Lubis et al (2021) stated that dry weight of rice and plant height that received ele ments increased under manure medium. Potassium reduces the negative effect of drought stress on leaf area index and plantʼs dry weight by increasing the ability of photosynthesis, the rate of CO 2 stabilizing with interference in osmosis, the activity of the enzyme Rubisco, and improving the synthesis and transport of dry matter (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nutrients on the soil surface are available for plant uptake (Zwieten, 2012). Besides, Lubis et al (2021) found that treatment with 50 g/polybag of biochar increased the corn plant height up to 176.17 cm. Adding biochar may retain more water and alter the pore space of the soil, allowing roots to grow freely and absorb many nutrients.…”
Section: Introductionmentioning
confidence: 98%